Formation of Monolayer Charge Density Waves and Anomalous Edge Doping in Na Doped Bulk VSe2 - Ulysse Chazarin; Mahé Lezoualc'h; Jyh‐Ping Chou; Woei Wu Pai; Abhishek Karn; Raman Sankar; Cyril C. Chacon; Yann Girard; Vincent Repain; Amandine Bellec; Sylvie Rousset; Alexander Smogunov; et al. (Advanced Materials Interfaces, 2023)
Abstract Alkali atom doping is an efficient way to induce charge transfer and Fermi level tuning in layered materials through intercalation. However, there is a general lack of microscopic understanding of the effect of doping inhomogeneity in geometric and electronic aspects. Here, we report surface doping of a bulk VSe2 crystal by sodium. Na atoms form intercalated subsurface islands that modify the electronic phase of the top layer of VSe2. In addition to n‐doping, the charge density wave of the intercalated VSe2 surface layer changes from the (4 × 4) bulk phase to the (3×7) known in monolayer phase of VSe2. Surprisingly, an electronic state at the edges of Na‐intercalated area shift anomalously upward in energy as detected by scanning tunneling spectroscopy. This is explained by a local gating effect resulting from local dipoles at the edges. The study illustrates a clear example of intercalation effect that should be general in alkali‐intercalated bulk layered materials.